Interdisciplinary Nature of Computational Science Cases in Business Studies - Husen, Amir; Chowdhury, Syed Mustafizur Rahman (Global Disclosure of Economics and Business, 2023)
The intricate confluence of computational science and business studies heralds an unprecedented era in the academic and industrial landscape. This paper comprehensively explores this interdisciplinary nexus, delving deep into the transformative potential that computational methodologies bring to business arenas. From leveraging vast datasets in business analytics to pioneering financial models, computational tools are reshaping the very paradigms of business decision-making. However, these advancements are not without challenges. Ethical considerations, over-reliance on models, and the essentiality of human insight remain critical discussions. Moreover, the paper underscores the need for further collaborative research, emphasizing the importance of a symbiotic relationship between computational scientists and business professionals. As the digital age progresses, integrating computational science into business studies becomes beneficial and imperative for organizations seeking innovative solutions and sustained growth in an increasingly complex market environment.